Closing Your Seasonal Home - Julie England; Audrey Norman; Randall A. Cantrell; Maria J. Portelos-Rometo (EDIS)
Get organized and make a plan before you lock your doors to leave your home for an extended period of time. Proper preparation inside and out will help ensure your return to a clean, undamaged home. Florida’s environment creates the possibility for mildew growth, storm damage, and pests. Unoccupied homes are more susceptible to these types of damage. This revised 6-page fact sheet provides the necessary steps to prepare your home before leaving for an extended period of time. There is also a checklist to help you remember. Written by Julie England, Audrey Norman, Randall A. Cantrell, and Maria J. Portelos-Rometo, and published by the UF Department of Family Youth and Community Sciences, June 2014.